Comparing treatment‐seeking codeine users and strong opioid users: Findings from a novel case series. (29th December 2014) - Nielsen, Suzanne; Murnion, Bridin; Dunlop, Adrian; Degenhardt, Louisa; Demirkol, Apo; Muhleisen, Peter; Lintzeris, Nicholas
Abstract Introduction and Aims Few studies have described those seeking treatment for codeine dependence. This study aimed to compare patients presenting for treatment where either codeine or a strong pharmaceutical opioid (oxycodone or morphine) was the principal drug of concern to understand if codeine users may have unique treatment needs. Design and Methods Retrospective case review of 135 patients from three geographical areas in New South Wales, Australia. Cases where the principal drug of concern was codeine (n = 53) or a strong pharmaceutical opioid (oxycodone or morphine, n = 82) were compared. Differences in demographic characteristics, pain history, mental health, substance use history and, subsequently, the treatment that was received were examined. Results People whose principal drug of concern was codeine were more likely to be female (66% vs. 37%, P < 0.001), employed (43% vs. 22%, P < 0.01) and use only one pharmaceutical opioid (91% vs. 49%, P < 0.001). There was no difference in age between the codeine group (mean 38.6 years) and the strong opioid group (39.3 years). Opioid substitution therapy was the most common treatment received by both groups although codeine patients were more likely to be treated with buprenorphine than methadone (odds ratio = 7.7, 95% confidence interval 2.2–27.2, P < 0.001) and more likely to attempt withdrawal (odds ratio = 2.6, 95% confidence interval 1.2–5.3, P = 0.010). Discussion and Conclusions There are important differences between codeine‐dependent patients and strong prescription opioid‐dependent patients. Further work should explore the outcomes of withdrawal versus maintenance treatment for codeine users. [Nielsen S, Murnion B, Dunlop A, Degenhardt L, Demirkol A, Muhleisen P, Lintzeris N. Comparing treatment‐seeking codeine users and strong opioid users: Findings from a novel case series. Drug Alcohol Rev 2014]